Validation of fish environmental RNA metabarcoding analysis for ecological surveys by additional traditional field surveys in the Naka River - Miyata, Kaede; Kusakabe, Yuta; Inoue, Yasuaki; Yamane, Masayuki; Honda, Hiroshi (Frontiers in Ecology and Evolution, 2025)
Metabarcoding analysis using fish environmental RNA (eRNA) has demonstrated higher performance compared to that using fish environmental DNA (eDNA) in the Naka River in Japan. However, the results from representative sampling sites were insufficient to estimate the diversity of organisms in the entire river. Therefore, we validated the evaluation performance using additional traditional field survey (TFS) data. Data from seven traditional field surveys on fish, covering the area near the sampling points where eDNA/eRNA metabarcoding analyses were conducted, were obtained. Ten fish species were newly identified, with nine determined using the eDNA and eRNA metabarcoding analyses. Performance was evaluated in terms of both positive predictive value (PPV) and sensitivity. Except for species specifically detected only near the estuary, the additional use of field survey data increased the PPV from 26.5% to 36.3% for eDNA and from 43.6% to 57.7% for eRNA. After combining the results of multiple surveys, the sensitivities for eDNA and eRNA increased from 52.4% to 67.4% and from 57.1% to 69.8%, respectively. The increase in PPV was more pronounced for eRNA than for eDNA, indicating that eRNA does not decrease PPV when multiple datasets are merged. The superior performance of eRNA compared to eDNA suggests that eRNA metabarcoding analysis is valuable for accurately conducting ecological surveys and biodiversity assessments and may reduce the labor required for monitoring the entire river by optimizing sampling points for metabarcoding analysis.